A study of the intermediate- to long-term outcome of corrosive ingestion in Swanpracharak Hospital. - Faknak, Natee; Singhattha, Anuch (Region 3 Medical and Public Health Journal - วารสารวิชาการแพทย์และสาธารณสุข เขตสุขภาพที่ 3, 2023)
Abstract Background/Aims: The ingestion of corrosive substances is linked to enduring consequences, particularly in cases with high-grade mucosal damage. This study aimed to examine the correlation between the severity of mucosal injury grading and the intermediate (more than one-month follow-up) to long-term outcomes (more than 12 months) following corrosive ingestion. Methods: Patients who presented with corrosive ingestion between January 2017 and December 2022 were included consecutively. A comprehensive review of medical records was conducted to gather information regarding the substance ingested, intent, symptoms, amount, injury grade at endoscopy, and clinical during follow-up. Results: During the study period, a total of 106 patients were admitted with corrosive ingestion, out of which 72 underwent esophagogastroduodenoscopy (EGD). Among the patients who underwent EGD, 19 (26.4%) were found to have high-grade esophageal lesions. The severity of gastrointestinal mucosal injury was not found to be related to the volume of ingestion or time to EGD, but upper gastrointestinal hemorrhage was significantly associated with high-grade esophageal injury and mortality. Three patients died during the index hospitalization, and the remaining patients were followed up for a median period of 821 days (14-1295), during which 18 patients were lost to follow-up before one year. During the intermediate-term follow-up, three patients with high-grade injuries died as a result of corrosive ingestion (length of hospital stay 45, 325, and 350 days, respectively), and four patients had significant esophageal strictures. Neither group exhibited any adverse consequences of corrosive ingestion during the long-term follow-up. Conclusions: Patients with high-grade esophageal mucosal lesions experienced significant morbidity and mortality during the intermediate-term follow-up. On the other hand, patients with low-grade esophageal injury did not exhibit any adverse consequences during the follow-up period. Therefore, after an endoscopy shows a low-grade esophageal mucosal lesion, patients can be treated as outpatients. The follow-up is not necessary after one year if the patients did not experience any adverse event. Keywords: corrosive ingestion, high-grade esophageal injury, esophageal stricture